Studi Literatur tentang Faktor-faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Pembayaran PBB (Pajak Bumi Bangunan) - Ivon, Ivon; Furqon, Imahda Khori (Department of Public Administration, 2025)
This study aims to examine the influence of income, tax sanctions, and tax knowledge on taxpayer compliance in the payment of Land and Building Tax (PBB) through a literature review approach. Taxpayer compliance in paying PBB is a crucial factor in supporting state revenue and regional development. The low level of compliance in Indonesia has led to suboptimal tax revenues. By reviewing various previous studies, this research finds that taxpayer income has a positive effect on compliance—higher income levels tend to correlate with greater compliance. Tax sanctions, although intended to serve as a deterrent, show no significant effect. Meanwhile, tax knowledge emerges as a key factor, with better-informed taxpayers demonstrating higher levels of compliance. The study concludes that these three variables have a complex and interrelated influence on compliance behavior. To enhance taxpayer compliance, it is recommended that tax authorities intensify education and outreach efforts while also enforcing tax sanctions more consistently and effectively.